1987
DOI: 10.1002/pola.1987.080251215
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and solid state 13C‐NMR studies of some cellulose derivatives

Abstract: SynopsisSeveral cellulose derivatives were synthesized and characterized by IR and 'H-NMR spectroscopy. T h e positions of substitution in these derivatives were confirmed using solid state I3C-NMR spectroscopy techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…As we all know, esterification of cellulose and its derivatives was carried out with acid chloride and pyridine or triethylamine as catalyst (Pawlowski et al 1987;Marsano et al 1998). However, acid chloride is sensitive to moisture and thionyl chloride corrodes the equipment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we all know, esterification of cellulose and its derivatives was carried out with acid chloride and pyridine or triethylamine as catalyst (Pawlowski et al 1987;Marsano et al 1998). However, acid chloride is sensitive to moisture and thionyl chloride corrodes the equipment.…”
Section: Resultsmentioning
confidence: 99%
“…The liquid crystalline behavior of cellulose derivatives has since aroused much interest in the field of liquidcrystalline polymers (Bhadani and Gray 1983;Isogai et al 1984;Pawlowski et al 1987;Yamagishi et al 1988;Chen et al 1992;Jiang and Huang 1993;Shaikh et al 1999;Huang et al 2007;Godinho et al 2009;Almeida et al 2009). During recent decades, several studies reported the introduction of the bulky and rigid mesogenic substituents on the cellulose backbone as side groups (Terbojevich et al 1999;Wu et al 2002Wu et al , 2003Wu et al , 2004Granström et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of esterification, however, is markedly decreased and the homologous compounds require more drastic conditions with increasing the chain length of carboxylic acid or using the aromatic acid. The esterification can be carried out by using acid chloride as the reagent and pyridine or triethylamine as chlorine hydride absorber,14, 15 but the acid chloride is more sensitive to moisture and the thionyl chloride can erode the equipment when it is removed from acid chloride under reduced pressure. Also, esterification of cellulose can be achieved by activating the carboxylic acids using DCC and DMAP as catalysts 16, 17.…”
Section: Resultsmentioning
confidence: 99%
“…TMSC was synthesized using the procedures of Pawlowski et al 5,6 from cellulose, DP 202 (Avicel, type PH-105, FMC Corp., Princeton, NJ), and DP 855 (Buckeye Cellulose, Memphis Tenn.). PAC was prepared using the Pawlowski et al procedure from cellulose DP 202, but triethylamine was used in place of pyridine as an acid acceptor.…”
Section: Methodsmentioning
confidence: 99%